APPROXIMATION OF THE DISTANCE IN THE PLANE THROUGH THE NUMERICAL SOLUTION OF INITIAL VALUE PROBLEMS ASSOCIATED TO GEODESICS - Rubio López, Franco (2015)
In this paper, we proposes an algorithm to approximate the Euclidean distance between points p and q of plane, by doing a search of geodesic that depart from the point p and arrive to a neighborhood of the point q . This search is done through the numerical solution of initial value problems associated with the system of ordinary differential equations of the geodesics; for this is choose a set of directions in the plane.